2012
DOI: 10.5194/acp-12-2899-2012
|View full text |Cite
|
Sign up to set email alerts
|

A-train CALIOP and MLS observations of early winter Antarctic polar stratospheric clouds and nitric acid in 2008

Abstract: Abstract. A-train Cloud-Aerosol Lidar with Orthogonal Polarization (CALIOP) and Microwave Limb Sounder (MLS)observations are used to investigate the development of polar stratospheric clouds (PSCs) and the gas-phase nitric acid distribution in the early 2008 Antarctic winter. Observational evidence of gravity-wave activity is provided by Atmospheric Infrared Sounder (AIRS) radiances and infrared spectroscopic detection of nitric acid trihydrate (NAT) in PSCs is obtained from the Michelson Interferometer for Pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
110
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(125 citation statements)
references
References 115 publications
(188 reference statements)
15
110
0
Order By: Relevance
“…These contours roughly represent the streamlines of the geostrophic wind and the NAT clouds are along contours crossing the AP region. These observations are in line with the mountain wave seeding hypothesis for PSCs as described and proofed with AIRS and MIPAS data by Eckermann et al (2010) or to the MIPAS NAT-belt events in mid-June 2003 and 2008 previously reported by Höpfner et al (2006b) and Lambert et al (2012), respectively. Preliminary analyses of all MIPAS and AIRS SH observations suggest that generally, the early winter conditions in mid-June facilitate meteorological conditions to form a mountain-wave-induced NAT belt (8 out of 10 winter).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These contours roughly represent the streamlines of the geostrophic wind and the NAT clouds are along contours crossing the AP region. These observations are in line with the mountain wave seeding hypothesis for PSCs as described and proofed with AIRS and MIPAS data by Eckermann et al (2010) or to the MIPAS NAT-belt events in mid-June 2003 and 2008 previously reported by Höpfner et al (2006b) and Lambert et al (2012), respectively. Preliminary analyses of all MIPAS and AIRS SH observations suggest that generally, the early winter conditions in mid-June facilitate meteorological conditions to form a mountain-wave-induced NAT belt (8 out of 10 winter).…”
Section: Discussionsupporting
confidence: 92%
“…Spang et al, , 2005Höpfner et al, 2006bHöpfner et al, , 2009Eckermann et al, 2009;Lambert et al, 2012;Arnone et al, 2012). Its main strength is the classification of clouds where the radiances are dominated by NAT particles with radii smaller than 3 µm (Höpfner et al, 2006a).…”
Section: Comparison Of 2cr and Bayesian Classifiermentioning
confidence: 99%
“…The use of Atmospheric Infrared Sounder (AIRS) observations for that purpose was first explored by Eckermann et al (2009) and Lambert et al (2012). In this paper, we present a new AIRS data set on gravity wave activity in the polar lower stratosphere that can be used to study the impact of gravity-waveinduced temperature fluctuations on PSC formation in more detail.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the approach used by Lambert et al (2012), P13, and Lambert and Santee (2017) transformed to T-T eq space, where T eq is defined as T NAT , T STS , or T ice , depending on the CALIOP composition classification, and is calculated using the Hanson and Mauersberger (1988) (T NAT ), Carslaw et al (1995) (T STS ), and Murphy and Koop (2005) (T ice ) relationships with the coincident MLS HNO 3 and H 2 O abundances. T eq for ice PSCs remains the same as in Figures 11(a) and 11(c) and the ice PSC distributions are identical to those in Figures 11(a) and 11(c).…”
Section: Consistency Of V2 Psc Observations With Expected Thermodynammentioning
confidence: 99%
“…prior to 2008 (see Lambert et al, 2012). The Aura MLS detects thermal microwave emission from the Earth's limb along the 5 line-of-sight in the forward direction of the Aura spacecraft flight track (Waters et al, 2006).…”
Section: Aura Mlsmentioning
confidence: 99%